2013
DOI: 10.1002/j.1532-2149.2013.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spinal cord stimulation frequency in experimental painful diabetic polyneuropathy

Abstract: The pain-relieving effect of SCS in PDP was studied in an experimental model. Our study shows that SCS on mechanical hypersensitivity in PDP rats is equally effective when applied at low, mid and high frequency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 32 publications
1
43
1
Order By: Relevance
“…In order to address this hypothesis, we implemented DRGS in an already operational and meticulously tested PDPN animal model and investigated the effectiveness of both DRGS and SCS. SCS and its resulting pain relief in streptozotocin (STZ)‐induced PDPN animals have recently been described and here it was shown that SCS normalizes STZ‐induced mechanical hypersensitivity . SCS resulted in “a clinically relevant reduction” of mechanical hypersensitivity in 70% of PDPN animals.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…In order to address this hypothesis, we implemented DRGS in an already operational and meticulously tested PDPN animal model and investigated the effectiveness of both DRGS and SCS. SCS and its resulting pain relief in streptozotocin (STZ)‐induced PDPN animals have recently been described and here it was shown that SCS normalizes STZ‐induced mechanical hypersensitivity . SCS resulted in “a clinically relevant reduction” of mechanical hypersensitivity in 70% of PDPN animals.…”
Section: Introductionmentioning
confidence: 74%
“…The experiments were approved by the Animal Research Committee of the Maastricht University Medical Centre (DEC‐protocol and approval (DEC 2013‐079)). The results of the experiments on these animals were compared to the results of a previous study investigating effect of conventional SCS but otherwise performed in an identical manner as this study (n = 8 for SCS and n = 3 for sham‐SCS) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this study, it was concluded that SCS is equally effective on mechanical hypersensitivity when applied at 4.0‐10 Hz, 35‐55 Hz, or 150‐375 Hz. Interestingly, use of SCS at LF (4.0‐10 Hz) did not result in a delayed wash‐out of analgesia after cessation of stimulation . As we did on the other hand observe a delayed wash‐out effect after LF‐DRGS in the current study, this effect may be related to the location of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Postligation, the wound was closed with a 4/0 silk suture, and the development of tactile hypersensitivity (mechanical allodynia) was monitored over the following 14 days. The presence of mechanical hypersensitivity was confirmed at 14 days post‐surgery, only if the log (50% withdrawal threshold [WT]) was decreased by 0.2 units compared to baseline (day 0) …”
Section: Methodsmentioning
confidence: 99%